2012
DOI: 10.1016/j.jcrc.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital amiodarone may increase the incidence of acute respiratory distress syndrome among patients at risk

Abstract: Purpose Amiodarone has been implicated as a risk factor for acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) when used in the hospital. This study aims to estimate whether prehospital amiodarone also increases the risk of ALI/ARDS. Materials Adult patients admitted to 22 centers with at least 1 risk factor for developing ALI were recruited. In a secondary analysis of this cohort, the prehospital use of amiodarone was documented on admission, and the patients followed for the primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is important to keep in mind that amiodarone-induced pulmonary fibrosis is a rare event that typically occurs after months to years of continued drug administration. It has also been shown that prehospital use of amiodarone may independently increase the risk for ARDS in patients with predisposing conditions for acute lung injury (ALI) [ 26 ]. Contributing factors to amiodarone-induced pulmonary toxicity include its direct cytotoxic effects (principally mediated by N -DEA), phospholipidosis, immunological mechanisms, and activation of the angiotensin system; however, the precise mechanisms contributing to amiodarone-induced pulmonary toxicity remain incompletely understood.…”
Section: Rationale For Amiodarone Usementioning
confidence: 99%
“…It is important to keep in mind that amiodarone-induced pulmonary fibrosis is a rare event that typically occurs after months to years of continued drug administration. It has also been shown that prehospital use of amiodarone may independently increase the risk for ARDS in patients with predisposing conditions for acute lung injury (ALI) [ 26 ]. Contributing factors to amiodarone-induced pulmonary toxicity include its direct cytotoxic effects (principally mediated by N -DEA), phospholipidosis, immunological mechanisms, and activation of the angiotensin system; however, the precise mechanisms contributing to amiodarone-induced pulmonary toxicity remain incompletely understood.…”
Section: Rationale For Amiodarone Usementioning
confidence: 99%
“…Amiodarone-associated ARDS has been reported in patients who have undergone surgery or pulmonary angiography though with limited literature. 2 Importantly, a prospective cohort study 3 reported that prehospital use of amiodarone increased nearly four times the odds of developing ARDS among patients at risk for acute lung injury (odds ratio = 3.8; 95% confidence interval 1.1–13.1). Indeed, the causative pathogen for COVID-19, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is able to induce acute lung injury in COVID-19 through down-regulation of angiotensin-converting enzyme 2.…”
mentioning
confidence: 99%